2020
DOI: 10.3389/fphys.2020.581843
|View full text |Cite
|
Sign up to set email alerts
|

Pax9’s Interaction With the Ectodysplasin Signaling Pathway During the Patterning of Dentition

Abstract: In these studies, we explored for the first time the molecular relationship between the paired-domain-containing transcription factor, Pax9, and the ectodysplasin (Eda) signaling pathway during mouse incisor formation. Mice that were deficient in both Pax9 and Eda were generated, and the status of dentition analyzed in all progeny using gross evaluation and histomorphometric means. When compared to wildtype controls, Pax9+/–Eda–/– mice lack mandibular incisors. Interestingly, Fgf and Shh signaling are down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…PAX9 is involved in the formation of the posterior teeth and mandibular incisors [26] , [29] . In vitro functional studies demonstrated that PAX9 null mutations reduced mRNA stability and protein production [15] , [19] , [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAX9 is involved in the formation of the posterior teeth and mandibular incisors [26] , [29] . In vitro functional studies demonstrated that PAX9 null mutations reduced mRNA stability and protein production [15] , [19] , [30] .…”
Section: Discussionmentioning
confidence: 99%
“…In hypomorphic mutants, third molar development was arrested prior to the bud stage, and that of the lower second molars was arrested at the bud stage, while the upper molars were less affected [26] . Furthermore, PAX9 functions in the mandibular incisor development involves the EDA pathway [29] . These findings indicate that reduced PAX9 gene dosage affects tooth development in multiple stages and the presence of a feedback mechanism and other signaling could affect the phenotypic consequence Pax9 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Pax9-dependent signaling is functionally integrated with EDA signaling during odontogenesis. 33 Treatment with anti-EDAR agonist antibody has been reported to resolve palate defects in Pax9 -/- mice, suggesting that the EDA/EDAR signaling pathway is downstream of Pax9. 34 There may be a unique interaction between Pax9 and the EDA signaling pathway that can be further exploited for the development of craniofacial complex.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that PAX9 was unable to fully compensate for the loss of PAX1 but PAX1 could fully rescue PAX9 deficiency during the vertebral column formation probably by its own expression level via a positive auto-feedback mechanism, suggesting PAX1 is the more dominant player in the axial skeleton development ( Peters et al, 1999 ; Sivakamasundari et al, 2017 ). Whereas, PAX9 plays essential roles in the palatogenesis and odontogenesis in which PAX1 is largely absent ( Peters and Balling, 1998 ; Kist et al, 2005 ; Zhou et al, 2013 ; Jia et al, 2020a ; Jia et al, 2020b ). In addition, PAX9 expression is not affected when PAX1 is mutated suggesting the expression of PAX9 is not dependent on PAX1 ( Neubüser et al, 1995 ; Sivakamasundari et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%